Background timing mismatch calibration technique for TIADC in Nyquist frequency band. Issue 15 (1st July 2020) - Yin, Yongsheng; Wan, Zhujuan; Chen, Hongmei; Liu, Lu; Deng, Honghui; Meng, Xu; Wu, Jingsheng
Abstract : A background calibration technique for time‐interleaved analogue‐to‐digital converter (TIADC) over Sub‐Nyquist frequency timing mismatch is proposed. When the input signal only satisfies the Nyquist sampling theorem of the overall TIADC rather than sub‐ADC, both directions of estimation based on correlation and compensation based on differentiator may be opposite to the actual value, which results in a failure calibration. In this Letter, the authors propose a calibration direction correction algorithm which can detect and correct the calibration direction and assure an effective calibration in the whole Nyquist frequency of TIADC. Simulation results show that, for a four‐channel 12‐bit 1 GS/s TIADC, with f in / f s = 0.45, signal to noise and distortion ratio (SNDR) is improved from 30.1 to 73.2 dB.